Uses and Misuses of Recorded Mental Health Lived Experience Narratives in Healthcare and Community Settings: Systematic Review. (23rd August 2021) - Yeo, Caroline; Rennick-Egglestone, Stefan; Armstrong, Victoria; Borg, Marit; Franklin, Donna; Klevan, Trude; Llewellyn-Beardsley, Joy; Newby, Christopher; Ng, Fiona; Thorpe, Naomi; Voronka, Jijian; Slade, Mike
Abstract: Mental health lived experience narratives are first-person accounts of people with experience of mental health problems. They have been published in journals, books and online, and used in healthcare interventions and anti-stigma campaigns. There are concerns about their potential misuse. A four-language systematic review was conducted of published literature characterizing uses and misuses of mental health lived experience narratives within healthcare and community settings. 6531 documents in four languages (English, Danish, Swedish, Norwegian) were screened and 78 documents from 11 countries were included. Twenty-seven uses were identified in five categories: political, societal, community, service level and individual. Eleven misuses were found, categorized as relating to the narrative (narratives may be co-opted, narratives may be used against the author, narratives may be used for different purpose than authorial intent, narratives may be reinterpreted by others, narratives may become patient porn, narratives may lack diversity), relating to the narrator (narrator may be subject to unethical editing practises, narrator may be subject to coercion, narrator may be harmed) and relating to the audience (audience may be triggered, audience may misunderstand). Four open questions were identified: does including a researcher's personal mental health narrative reduce the credibility of their research?: should the confidentiality of narrators be protected?; who should profit from narratives?; how reliable are narratives as evidence?)